2015
DOI: 10.1186/s13023-015-0369-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence, and age at diagnosis in Marfan Syndrome

Abstract: BackgroundMarfan syndrome is a genetic disorder with considerable morbidity and mortality. Presently, clinicians use the 2010 revised Ghent nosology, which includes optional genetic sequencing of the FBN1 gene, to diagnose patients. So far, only a few studies based on older diagnostic criteria have reported a wide range of prevalence and incidence. Our aim was to study prevalence, incidence, and age at diagnosis in patients with Marfan syndrome.MethodUsing unique Danish patient-registries, we identified all po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
115
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(129 citation statements)
references
References 28 publications
6
115
1
7
Order By: Relevance
“…One study found EL in 38% of neonates and another study reported that MFS was diagnosed in patients at zero age, but did not specify if EL was present at birth. 2,23 Other studies have not found EL before the age of 18 months. 24,25 Studies in different age groups have reported a frequency of EL in children younger than 10 years from 63% to 75% and younger than 17 years from 15% to 57%.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…One study found EL in 38% of neonates and another study reported that MFS was diagnosed in patients at zero age, but did not specify if EL was present at birth. 2,23 Other studies have not found EL before the age of 18 months. 24,25 Studies in different age groups have reported a frequency of EL in children younger than 10 years from 63% to 75% and younger than 17 years from 15% to 57%.…”
Section: Discussionmentioning
confidence: 92%
“…There is a reason to believe that EL may be present from birth in some MFS patients. One study found EL in 38% of neonates and another study reported that MFS was diagnosed in patients at zero age, but did not specify if EL was present at birth . Other studies have not found EL before the age of 18 months .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A revision of the cancer penetrance of these disorders is needed. Well-known, highly penetrant genetic disorders with population prevalence frequencies spanning our DICER1 pathogenic variation estimates include sickle cell anemia (1/500 African American births) 33 , Down syndrome (1/700 live births) 34 , velo-cardio-facial syndrome (1/2,000) 35 , cystic fibrosis (1/2,500 white Americans) 36 , neurofibromatosis type 1 (1/3,000) 37 , and Duchenne muscular dystrophy (1/5,000 – 1/7,500 boys) 38 , hemophilia A (factor VIII deficiency; 1/6,500 live male births) 39 , Williams syndrome (1/7,500) 40 and Marfan syndrome (1/7,500 – 1/10,000) 41 . As noted, the penetrance related to the pathogenic DICER1 variants we have reported here needs to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, our study was limited to patients with MFS and BAV, so our findings may not necessarily be applicable to other cohorts. However, MFS is a leading etiology of geneticallyassociated TAA, affecting up to 65,000 individuals in the United States and 1,400,000 worldwide (23). Moreover, our findings provide important hypothesis-generating data concerning aortic stiffening as a novel predictor of TAA growth that can be broadly tested in future studies encompassing cohorts with both genetic and sporadicallymediated TAA.…”
Section: Limitationsmentioning
confidence: 95%